2021
DOI: 10.1167/tvst.10.11.1
|View full text |Cite
|
Sign up to set email alerts
|

On Clinical Agreement on the Visibility and Extent of Anatomical Layers in Digital Gonio Photographs

Abstract: Purpose To quantitatively evaluate the inter-annotator variability of clinicians tracing the contours of anatomical layers of the iridocorneal angle on digital gonio photographs, thus providing a baseline for the validation of automated analysis algorithms. Methods Using a software annotation tool on a common set of 20 images, five experienced ophthalmologists highlighted the contours of five anatomical layers of interest: iris root (IR), ciliary body band (CBB), sclera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Comparing average per-layer metrics on the hold-out test set (table 2) between the two models, our new one returned overall higher Dice scores, in particular for CBB and SS (+2.4% and +5.6% on average), two layers of fundamental clinical importance. To interpret these values correctly, one must consider that, importantly, the average inter-observer Dice scores for CBB and SS reported in our pilot inter-annotator variability study 17 were about 75% and 65% (the lowest), making our results consistent with the average agreement between experts. Our previous approach promoted sensitivity (less false negatives) for layers with lower inter-annotator agreement (CBB and SS) while the new one promotes precision (less false positives).…”
Section: Figuresupporting
confidence: 68%
See 2 more Smart Citations
“…Comparing average per-layer metrics on the hold-out test set (table 2) between the two models, our new one returned overall higher Dice scores, in particular for CBB and SS (+2.4% and +5.6% on average), two layers of fundamental clinical importance. To interpret these values correctly, one must consider that, importantly, the average inter-observer Dice scores for CBB and SS reported in our pilot inter-annotator variability study 17 were about 75% and 65% (the lowest), making our results consistent with the average agreement between experts. Our previous approach promoted sensitivity (less false negatives) for layers with lower inter-annotator agreement (CBB and SS) while the new one promotes precision (less false positives).…”
Section: Figuresupporting
confidence: 68%
“…In a previous study, we have reported a detailed analysis on the inter-annotator variability of anatomical layers delineations in digital gonio-photographs. 17 In essence, we observed lower average agreement (quantified using Dice scores) for CBB and SS (about 75% and 65%, respectively) than for I, TM and C (about 97%, 87% and 95%, respectively). This will be important when assessing system performance.…”
Section: Data Selection and Characteristicsmentioning
confidence: 65%
See 1 more Smart Citation
“…Digital gonioscopy has been shown useful in documenting post-operative and abnormal findings of the ACA and has a great potential for teaching gonioscopy. Deep learning algorithms for automatic classification of the angle are on the horizon and their validity in the clinical setting should be accurately evaluated [31][32][33]. Informed Consent Statement: Written informed consent has been obtained from the patients to publish images in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Peroni et al recently better characterized the agreement on identification of the ACA structures between graders. Using a software annotation tool that permitted tracing the contours of anatomical layers, Peroni et al found that scleral spur had the minimum agreement whereas it was best on iris root, trabecular meshwork and cornea [ 31 ]. Based on these studies, deep learning semantic segmentation algorithms for processing images acquired by GS-1 are currently in development [ 32 , 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%